Convergence Rate of Empirical Bayes for Two-Parameter Exponential Distribution with Replicated Data (Communications in Mathematical Research, 2021)
In this paper, empirical Bayes test for a parameter $θ$ of two-parameterexponential distribution is investigated with replicated past data. Under some conditions, the asymptotically optimal property is obtained. It is indicated that the rate ofconvergence can be very close to $O(N^{−\frac{1}{2}})$ in this case that a parameter $µ$ is known.
Keywords: replicated data; empirical Bayes; asymptotic optimality.